Pengaruh Media Sosial Instagram Terhadap Minat Beli Konsumen Secara Offline - Marlina Marlina; Fitriliana Fitriliana; Juwita Juwita; Putri Mauliza; Filia Hanum (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
In the digital era, Instagram has become a dominant platform in product marketing, enabling companies to reach a wider audience through engaging visual content. Although interactions and transactions often occur online, consumer purchasing interest in making purchases in physical stores remains significant. The research method used is field research with an associative quantitative approach, the sources of research information are basic information and secondary information. Information in this study was collected using a questionnaire technique, and after the data was collected. The results of this study are to explain the influence of Instagram social media on consumer purchasing interest. The results show that Instagram social media has a positive and significant effect on consumer purchasing interest, indicated by the t-test coefficient value of Instagram social media with a t-table value of (4.298> 0.05). And the magnitude of the influence obtained from the coefficient of determination value of 0.631 is equal to 63.1%. This value indicates that 63.1% of consumer purchasing interest is influenced by Instagram social media while the remaining 36.9% is influenced by other factors. The research method used is a survey with a questionnaire distributed to 200 respondents who actively use Instagram and make purchases offline. The information obtained was analyzed using regression analysis to measure the relationship between the independent variable (Instagram usage) and the dependent variable (offline purchase intention). The results showed a significant positive effect between Instagram social media and offline consumer purchase intention. Engaging content, positive interactions, and effective promotions on Instagram have been shown to increase consumer interest in making purchases in physical stores. This research provides a compelling impetus for businesses to formulate marketing strategies that leverage the power of social media to increase offline sales.